2023
DOI: 10.1083/jcb.202205004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pruning of sensory neurites by mechanical tearing in Drosophila

Abstract: Mechanical forces actively shape cells during development, but little is known about their roles during neuronal morphogenesis. Developmental neurite pruning, a critical circuit specification mechanism, often involves neurite abscission at predetermined sites by unknown mechanisms. Pruning of Drosophila sensory neuron dendrites during metamorphosis is triggered by the hormone ecdysone, which induces local disassembly of the dendritic cytoskeleton. Subsequently, dendrites are severed at positions close to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Why a role for neuron-autonomous EcR signaling is more fully revealed when astrocytes are also blocked from transformation is an open question. A recent study showed that neuronal ecdysone signaling allows ddaC neurons to become competent for pruning by driving microtubule rearrangement, with subsequent physical force caused by tissue movement in the body wall during metamorphosis driving the severing and fragmentation of dendrites (Krämer, Wolterhoff et al 2023). It is possible that neuronal ecdysone signaling may make Beat-Va M neurons competent for remodeling through similar mechanisms, but execution of fragmentation requires a secondary mechanical event.…”
Section: Discussionmentioning
confidence: 99%
“…Why a role for neuron-autonomous EcR signaling is more fully revealed when astrocytes are also blocked from transformation is an open question. A recent study showed that neuronal ecdysone signaling allows ddaC neurons to become competent for pruning by driving microtubule rearrangement, with subsequent physical force caused by tissue movement in the body wall during metamorphosis driving the severing and fragmentation of dendrites (Krämer, Wolterhoff et al 2023). It is possible that neuronal ecdysone signaling may make Beat-Va M neurons competent for remodeling through similar mechanisms, but execution of fragmentation requires a secondary mechanical event.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrite severing in the C4da neurons takes place during the period of elevated movements of pupal tissue, which applies mechanical forces to break dendrites. This suggests that mechanical tearing may be a novel mechanism underlying dendrite pruning [ 62 ]. It has been found that the axons and proximal regions of dendrites in C4da neurons are encapsulated by peripheral glial cells [ 63 ], and thus mechanical dendritic dissection during pruning may be affected by these surrounding cells.…”
Section: Polycomb Group (Pcg) Proteins Mechanical Forces and Translat...mentioning
confidence: 99%
“…Cell biological pathways underlying neurite pruning therefore must involve mechanisms for spatial regulation of neurite destruction and maintenance. This spatial aspect of pruning may in part be due to cytoskeleton regulation [ 2 ] and tissue mechanical aspects [ 3 ]. Following pruning, remodeling neurons often regrow new neurites with a morphology adapted to subsequent developmental stages.…”
Section: Introductionmentioning
confidence: 99%